Pumping the Periosteum: A Feasibility Study. Issue 2 (10th August 2022) - Saulacic, Nikola; Vunjak-Novakovic, Gordana; Haga-Tsujimura, Maiko; Nakahara, Ken; Gerbaix, Maude Coline; Ferrari, Serge Livio
Abstract : Purpose: Gradual elevation of periosteum from the bone surface is known to promote the adaptation of soft tissues and the formation of hard tissues. The aim of our study was to estimate the benefit of periosteal distraction osteogenesis (PDO) on de novo bone formation in a rat model. Materials and Methods: After device placement, animals were allowed for a latency period of 7 days. Animals in the PDO group were subjected to distraction at a rate of 0.1 mm/d for 10 days. In the periosteal pumping (PP) group, the animals were subjected to distraction at a rate of 0.1 mm/d. The direction of distraction was alternated every 2 days. The animals were euthanized at 17, 31, and 45 days after surgery, and the samples were analyzed histologically and by microcomputed tomography. Results: In both groups, the new bone was characterized as primary woven bone that was located at the leading edge of bone apposition. Bone volumes significantly increased throughout the observation period both in the PP group ( P = 0.018) and in the PDO group ( P < 0.001). The new bone was denser and more mature in the PP group than in the PDO group, and the difference was significant at the 31-day time point ( P = 0.024). However, the volume of the new bone was higher in the PDO at the 45-day time point ( P < 0.001). Conclusions: We propose that the PP may be applied to enhance the osteogenic capacity of periosteum without plate elevation. Because this is only a proof-of-principle study, the alternated protocol of periosteal distraction warrants evaluation in the future studies.